Observation of Augmented Reality in Teaching Physics as a tool of Intelectual Teaching (Journal of Educational Sciences, 2022)
This article complements and explores the use of augmented reality technologies in education as an example. The main task of the study was to find and study the advantages and disadvantages of teaching methods in physics, known and previously developed in physics, using AR and VR, in terms of their use for educational purposes. The purpose of the work is to review the analytical literature and analyze the known methods of using augmented and virtual reality, to suggest the most promising solutions to various scientific problems. The possibilities of advanced reality technology in the article allow you to integrate it into training and design activities. This article presents the use of stereometry and space in the technology of augmented reality in physics, in particular in the study of bodies. There is something that allows you to interact directly with the figures, look at them from different angles and call them the necessary information. The importance of teacher training in the use of augmented reality technology in the teaching process was identified. It was also noted that in the process of creating AR applications, the student can successfully participate in project activities. The research materials for webofscience and Scopus licensed foreign databases were used as research materials for keywords. Approaches to teaching methods using complementary and virtual reality technologies are considered. Defines the type of modern ways of teaching physics to pupils and students through augmented and virtual reality technologies.Keywords: augmented reality, physics, education.